148k views
4 votes
Help me out in this que ....Thank you​

Help me out in this que ....Thank you​-example-1
User BMeph
by
5.6k points

2 Answers

3 votes

see the attached solution

Help me out in this que ....Thank you​-example-1
2 votes

Answer:


(-2x^4-6)/((x+1)(x-1)(x^2+1))

Explanation:

Given expression:


(2)/(x+1)-(2x)/(x-1)+(4)/(x^2+1)

The least common multiplier of the denominators is:


(x+1)(x-1)(x^2+1)

Adjust the fractions based on the least common multiplier:


\implies (2(x-1)(x^2+1))/((x+1)(x-1)(x^2+1))-(2x(x+1)(x^2+1))/((x+1)(x-1)(x^2+1))+(4(x+1)(x-1))/((x+1)(x-1)(x^2+1))


\textsf{Apply the fraction rule}: \quad (a)/(c) \pm (b)/(c)=(a \pm b)/(c):


\implies (2(x-1)(x^2+1)-2x(x+1)(x^2+1)+4(x+1)(x-1))/((x+1)(x-1)(x^2+1))

Simplify:


\implies (2(x^3-x^2+x-1)-2x(x^3+x^2+x+1)+4(x^2-1))/((x+1)(x-1)(x^2+1))


\implies (2x^3-2x^2+2x-2-2x^4-2x^3-2x^2-2x+4x^2-4)/((x+1)(x-1)(x^2+1))


\implies (-2x^4+2x^3-2x^3-2x^2-2x^2+4x^2+2x-2x-2-4)/((x+1)(x-1)(x^2+1))


\implies (-2x^4-6)/((x+1)(x-1)(x^2+1))

User Cary
by
5.5k points